PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI PERSEDIAAN PADA ONLINE SHOP QIN’S APPAREL - Upayarto, Budi; Nurma’rufah, Novia (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2022)
Qin's Apparel is a business manufacturing that processes the purchase of raw materials and then orders craftsmen and sells them. The system currently used is by recording books that are still incomplete, resulting in inaccurate stock information and uncontrolled sales returns. This causes ineffectiveness in managing inventory, the resulting information is also less reliable. The method used in designing and implementing the system on Qin's Apparel is a descriptive method, with the PIECES system analysis method and the system development method using the waterfall. Meanwhile, to assist in making this application, the author uses the literature study method, namely reading and understanding the theories obtained from books and the internet related to this Final Project. With the system that is designed and implemented, it is expected that the inventory information system can process and process data that has been entered faster, the level of input and calculation errors is lower, data storage and data retrieval can be carried out in the past. Thus, it is expected to provide relevant, accurate, and up to date information that can be used for the benefit of the company.